Analisis Bibliometrik Terhadap kemampuan Pemahaman Konsep Matematis - Syafitri, Marliza; Zulfah; Astuti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The purpose of this bibliometric analysis is to see opportunities and developments in research trends related to the ability to understand mathematical concepts. This research uses bibliometric analysis method. The data in this study were obtained through Google from 2018 – 2023 with the keyword ability to understand mathematical concepts. Researchers analyzed 1000 original articles from 2018 - 2023. This study used PoP and VOSviewers software to analyze the data. Based on the findings and results and discussion, it was found that the highest number of scientific publications on the Google Scholar website from 2018-2023 occurred in 2019. The research results based on overlay visualization and density visualization in 2018-2023 focused on mathematical concept variables, meaning that many studies have been conducted by other researchers.